Parenting Pattern in Instilling The Character for Children From an Early Age - Dharlinda Suri (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The educational process starts from the family, so that the family becomes a good place to teach moral values and good character education. This research is aimed at knowing the parental roles in developing the children’s character since early age in Bakung Ilir Gedong Meneng. The reseasrch used qualitative method with fenomenology method which focused on natural paradigm based on the fenomenolgy point of view. The research findings shows that the caring model of families in inplanting the charachter to children of early age in Bakung Ilir as follows: (1) inplanting the religious values to children, (2) inplanting the moral values, (3) the way how the children behave in their daily activities, (4) training children’s intrerests and talent, (5) teaching bravey to children, (6) training responsibility to children, and (7) training independent life to children. The family is the first learning environment that children get and will be a strong foundation to shape character in the future.